Teachers' Perceptions of The Implementation of Merdeka Curriculum In English Language Learning At Phase EO F Madrasah Aliyah Mathla'ul Anwar Pusat Menes Pandeglang Banten - Imas Masitoh (Journal of English Education Studies, 2024)
This research aims to explore and analyze teachers' perceptions of the implementation of the Merdeka Curriculum on English subjects in phase E at Madrasah Aliyah Mathla'ul Anwar, Menes Pusat. The Merdeka Curriculum was introduced as a government effort to increase the relevance and quality of education in Indonesia. Phase E in Madrasah Aliyah Mathla'ul Anwar refers to the upper secondary education level. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with English teachers involved in implementing the Merdeka Curriculum in phase E. Data analysis was carried out using a thematic approach to identify main patterns in teacher perceptions. The research results show that the majority of teachers have a positive perception of the implementation of the Merdeka Curriculum in English subjects in phase E of Madrasah Aliyah Mathla'ul Anwar. They see the Merdeka Curriculum as a progressive step that provides flexibility in teaching and assessment methods. The application of a scientific approach and contextual learning is considered to enrich students' learning experiences. However, a number of teachers also face challenges in implementing the Merdeka Curriculum. Some of them feel there is a lack of infrastructure support and supporting resources, such as textbooks that are in accordance with the Merdeka Curriculum approach. Additionally, rapid curriculum changes create confusion and concerns regarding proper understanding and implementation. Meanwhile, the assessment aspect is a major concern for English teachers. They consider that the assessment system integrated in the Merdeka Curriculum needs to be adjusted to better support the learning approach promoted. Some teachers also voiced the need for further training to understand and implement the Merdeka Curriculum effectively. In conclusion, teachers' perceptions of the implementation of the Merdeka Curriculum in English subjects in phase E of Madrasah Aliyah Mathla'ul Anwar reflect a combination of appreciation for innovation and challenges in its implementation. Further efforts are needed to support teachers in overcoming the barriers they face, including the provision of adequate resources and relevant training. This study provides valuable insights for the development and improvement of the implementation of the Merdeka Curriculum in the context of Aliyah madrasah education.